Teaching to transgress: Education as the practice of freedom - Hooks, Bell (London Routledge, 1994)
Teaching to Transgress: Education as the Practice of Freedom In Teaching to Transgress, bell hooks--writer, teacher, and insurgent black intellectual--writes about a new kind of education, education as the practice of freedom. Teaching students to "transgress" against racial, sexual, and class boundaries in order to achieve the gift of freedom is, for hooks, the teachers most important goal.